Liver Transplantation in India: At the Crossroads - Nagral, Sanjay (J Clin Exp Hepatol, 2015)
As the liver transplant journey in India reaches substantial numbers and suggests quality technical expertise, it is time to dispassionately look at the big picture, identify problems, and consider corrective measures for the future. Several features characterize the current scenario. Although the proportion of deceased donor liver transplants is increasing, besides major regional imbalances, the activity is heavily loaded in favor of the private sector and live donor transplants. The high costs of the procedure, the poor participation of public hospitals, the lack of a national registry, and outcomes reporting are issues of concern. Organ sharing protocols currently based on chronology or institutional rotation need to move to a more justiciable severity-based system. Several measures can expand the deceased donor pool. The safety of the living donor continues to need close scrutiny and focus. Multiple medical challenges unique to the Indian situation are also being thrown up. Although many of the deficits demand state intervention and policy changes the transplant community needs to take notice and highlight them. The future of liver transplantation in India should move toward a more accountable, equitable, and accessible form. We owe this to our citizens who have shown tremendous faith in us by volunteering to be living donors as well as consenting for deceased donation.